THE EFFECT OF DIRECT AND INDIRECT COMPENSATION TO MOTIVATION AND LOYALTY OF THE EMPLOYEE - W, M. Abdi Dzil Ikhram; Armanu, Armanu; Sudjatno, Sudjatno (Jurnal Aplikasi Manajemen, 2017)
This study aimed to determine the effect of direct and indirect compensation to motivation and loyalty of the employee. Direct compensation based on indicators of salaries, incentives, and payment delays and indirect compensation is based on indicators of Time-Off Benefits, protection against danger, program benefits, and legal services then the motivation as a mediating variable. The Population in this study were 46 employees of the representative office of Bank Indonesia Kediri. This study used the saturated sample and the sample size in this study were 46 employees of a representative office of Bank Indonesia Kediri. Data analysis performed by linearity test and test hypotheses using path analysis. The results showed that the variable compensation is not directly significant effect on loyalty and motivation of the employee. The variable compensation also an indirectly significant effect on employee loyalty through employee motivation. Independent variables on loyalty and employee motivation are 77%, while the remaining 33% is influenced by other variables not examined in this study.